1988
DOI: 10.1073/pnas.85.4.1052
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant vaccinia virus vaccine against the human melanoma antigen p97 for use in immunotherapy.

Abstract: We have constructed a recombinant vaccinia virus, v-p97NY, which expresses the human melanomaassociated glycoprotein p97. Immunization with v-p97NY could induce humoral and cell-mediated immunity to p97, including delayed-type hypersensitivity, in mice and in two of two monkeys (Macaca fascicularis). The fact that an immune response was induced also in monkeys is important because normal cells from monkeys, but not from mice, express a low level of cross-reactive p97. Mice immunized with v-p97NY rejected trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

1991
1991
2005
2005

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(18 citation statements)
references
References 30 publications
0
18
0
Order By: Relevance
“…42,44,46,57 -59 In some of those studies, costimulatory molecules or cytokines were used to enhance vaccine effects. 44,45,59,64 These studies have suggested a role for antibodies, 36 -41,43,47,48,51 -53,60,63,64 CTL, 36 -48 and delayed-type hypersensitive T cells, 36,37,46,53 although the role of these factors was not directly demonstrated by in vivo cell depletion or adoptive cell transfer. The mouse models targeting human carcinoembryonic Ag (CEA ) and MUC-1 with VV vaccines, 36,39 -41,43,45 -48,52,63 similar to the human GA733 model used in the present study, include Ags that are expressed by tumors and by normal tissues.…”
Section: Cancer Gene Therapymentioning
confidence: 99%
“…42,44,46,57 -59 In some of those studies, costimulatory molecules or cytokines were used to enhance vaccine effects. 44,45,59,64 These studies have suggested a role for antibodies, 36 -41,43,47,48,51 -53,60,63,64 CTL, 36 -48 and delayed-type hypersensitive T cells, 36,37,46,53 although the role of these factors was not directly demonstrated by in vivo cell depletion or adoptive cell transfer. The mouse models targeting human carcinoembryonic Ag (CEA ) and MUC-1 with VV vaccines, 36,39 -41,43,45 -48,52,63 similar to the human GA733 model used in the present study, include Ags that are expressed by tumors and by normal tissues.…”
Section: Cancer Gene Therapymentioning
confidence: 99%
“…The ability of poxviruses to induce strong CTL responses has led to consideration of their use as cancer vaccines. Recombinant vaccinia viruses that express viral antigens (101,112) or cellular tumor-associated antigens (113)(114)(115)(116) have provided prophylactic and therapeutic effects against experimental tumors. Cytokines (IL-2 and IL-12) and/or costimulatory molecules (B7-1 and B7-2) may enhance the immune effects in model systems (117,118).…”
mentioning
confidence: 99%
“…Despite the expression of trace amounts of cross-reactive melanotransferrin in normal tissues of primates, no adverse effects or normal tissue damage could be observed after eliciting the immune response against melanotransferrin (53). This suggests that vaccination with melanotransferrin (668-683) against melanotransferrin-expressing tumors may also be safely applicable in man.…”
Section: Discussionmentioning
confidence: 78%
“…Early studies using recombinant vaccinia virus vaccines against melanotransferrin in mice and Macaca fascicularis monkeys have shown that cell-mediated and humoral immune responses could be induced against melanotransferrin-expressing xenografts and transfected syngeneic tumor cells resulting in in vivo rejection of tumor cells (53,54). Despite the expression of trace amounts of cross-reactive melanotransferrin in normal tissues of primates, no adverse effects or normal tissue damage could be observed after eliciting the immune response against melanotransferrin (53).…”
Section: Discussionmentioning
confidence: 99%